Tatwir Al Mawad Ad Dirasiyyah 'ala kitab Al Lughah Al 'arabiyyah fii Madrasah Ibtidaiyyah li Fashli Al Awwal - Ahmad Mujahid (Jurnal Al-Maqoyis, 2019)
Teaching materials are one of the important components in the learning process. Teaching materials contain materials that will be delivered in the learning process. The purpose of developing teaching materials in this research is so that the teaching materials used can be more systematic and in accordance with the development of students. The method used in this research is Research and Development. The book developed is an Arabic language book for Madrasah Ibtidaiyah grade 1 used at Madrasah Ibtidaiyah Al Hidayah Babayau with the title 'Ayo Belajar Bahasa Arab untuk MI Kelas 1'. This research is only up to material development. The results of this research are the addition of material, changing the material, changing the composition of the material.